Vulvar mpox lesions in a heterosexual cisgender woman with molecular biology and electron microscopy findings: case report - Passos, Mauro Romero Leal; Arze, Wilma Nancy Campos; Paixão, Izabel Christina Nunes de Palmer; Pessanha, Claudio Cesar Cirne dos Santos; Barros , Caroline de Souza; Rabelo, Kíssila; Carvalho, Jorge José de; Varella, Renata de Queiroz; Passos, Carolina Varella Leal; Passos, Paula Varella Leal; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2025)
Introduction: Mpox, an emerging viral zoonosis, caused a global outbreak in 2022, exhibiting patterns of interpersonal transmission distinct from those observed in previous outbreaks. While the initial focus was on transmission among men who have sex with men, the occurrence and clinical characteristics of mpox in women remain poorly understood. Objective: To describe a case of vulvar lesions in a heterosexual cisgender woman diagnosed with mpox. Methods: This is the case of a heterosexual cisgender woman with vulvar lesions confirmed as mpox, who was treated at the Sexually Transmitted Diseases Sector of the Fluminense Federal University. Results: A 29-year-old cisgender heterosexual woman presented with vulvar lesions confirmed as mpox. The patient reported a history of attending crowded places in the period before the onset of lesions. Diagnostic confirmation was achieved by molecular biology (real-time polymerase chain reaction) and electron microscopy. Conclusion: This case highlights the importance of considering mpox in the differential diagnosis of genital lesions in women and reinforces the need for a comprehensive approach to the surveillance and understanding of the disease’s epidemiology across diverse populations.